AZOTOBACTER AND CHEMICAL FERTILIZER FOR IMPROVING GROUNDNUT YIELD IN FIELD EXPERIMENT - Reginawanti Hindersah; Agung Muhammad Yusuf; Dewikusuma Ikhsani Adhiningtyas; Diyan Herdiyantoro; Oviyanti Mulyani; Pujawati Suryatmana (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2024)
Biofertilizer inoculation is a novel and sustainable approach for reducing chemical fertilizer dose. The nitrogen-fixing Azotobacter is a prominent rhizobacteria used in biofertilizer formulation. A field experiment was aimed to observe the N availability, N uptake, nodulation, and growth and yield of groundnuts grown with A. chroococcum liquid inoculant and reduced dose of NPK fertilizer. The field experiment was arranged in a Randomized Block Design to test eight combination treatments of A. chroococcum inoculant doses (2 and 3 L/ha) and NPK fertilizer doses (75, 150 and 300 kg/ha). Azotobacter and NPK application did not affect plant height at two and three weeks after sowing. Groundnuts treated with 2 L/ha Azotobacter combined with 150 kg/ha NPK had more NO3- in soil, N uptake, and root dry weight; its pod number and weight per plot increased 110% and 40% than that in plot received 2L/ha Azotobacter and 300 kg/ha NPK respectively. The experiment found that A. chroococcum shall replace part of NPK fertilizer for growing groundnut in Inceptisols soil order.